(untitled) (Al-Aasar, 2025)
The historic sermon of the farewell pilgrimage delivered by the Prophet Muhammad (peace be upon him), encompassing human rights, continues to hold precedence in the realm of human rights documents, emphasizing respect for humanity and the preservation of rights amidst a series of contradictions. It extends superiority over all human rights charters and documents from the inception to the advancement of human rights in the Western world. In this exemplary and historic sermon, you did not confine yourself to mere formal decrees and implementation of the Charter of Human Rights! Rather, you ensured effective and relevant practical measures for its preservation and enforcement, thereby establishing its implementation in your blessed life within your established Medina society. The farewell sermon of the Prophet Muhammad (peace be upon him) also gains precedence because the Charter bestowed by you holds a universal and global significance. You were not just a Prophet for the Arabs; you emerged as a universal guide, bringing the universal religion of Islam and eternal teachings to guide humanity globally. You granted the descendants of Adam exemplary and universal rights and duties, which are not merely theoretical concepts or ideas like Western legal theories but are rather a guarantor of human welfare and righteousness, a manifesto of humanity.